Effect of SMES Unit on the Performance of Type-4 Wind Turbine Generator during Voltage Sag - Yunus, Andi M.; Abu Siada, Ahmed; Masoum, Mohammed (IET, 2011)
Direct-drive variable speed wind turbine with full scale converter or so-called type-4 wind turbine generator has been installed increased to about 20.3% worldwide in 2002. Voltage sag in the grid side may cause the wind turbine to be disconnected from the grid. In this paper, Superconducting Magnetic Energy Storage (SMES) unit is applied to improve the fault ride through capability of type-4 wind turbine during voltage sag in the grid side. Simulation is carried out using MATLAB/Simulink software and the results show that SMES unit can significantly improve the performance of type-4 wind turbine and prevent it from being disconnected during a certain degree of voltage sag depth in the grid side.